Residual SYNTAX Score and One-Year Outcome in Elderly Patients With Acute Coronary Syndrome - Morici, Nuccia (CJC Open, 2020)
BACKGROUND: The residual burden of coronary artery disease after percutaneous coronary intervention (PCI) has been associated with worse ischemic outcome. However, data are conflicting in elderly patients. The aim of our study was to verify the incremental value of the residual Synergy Between Percutaneous Coronary Intervention With Taxus and Cardiac Surgery (SYNTAX) score (rSS) over clinical variables and baseline SYNTAX score (bSS) in predicting 1-year mortality or cardiovascular events. METHODS: A post hoc analysis of data collected in the Elderly-ACS 2 multicenter randomized trial was performed. We included 630 patients aged > 75 years with multivessel coronary disease undergoing PCI for acute coronary syndrome (ACS). The primary outcome was a composite of death, recurrent myocardial infarction, and stroke at 1-year follow up. Change in c-statistic and standardized net benefit were used to evaluate the incremental value of the rSS. RESULTS: Event rates were significantly higher in patients with incomplete revascularization (rSS > 8). When the rSS was included in a core Cox regression model containing age, previous myocardial infarction, and ACS type, the hazard ratio for patients with score values > 8 was 2.47 (95% confidence interval, 1.51-4.06). However, the core model with rSS did not increase the c-statistic compared with the core model with the bSS (from 0.69 to 0.70) and gave little incremental value in the standardized net benefit. CONCLUSIONS: In elderly patients with ACS with multivessel disease undergoing PCI, incomplete revascularization was associated with worse outcome at 1-year follow-up. However, there was no clear incremental value of the rSS in the prediction of 1-year adverse outcome compared with a model including clinical variables and bSS.